2011
DOI: 10.1039/c0nr00779j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative biodegradation of single- and multi-walled carbon nanotubes

Abstract: In this study we compare the biodegradation of both single-walled (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) using two different oxidative conditions. In particular, we demonstrate that oxidized multi-walled carbon nanotubes are highly degraded, although not to completeness when treated with horseradish peroxidase (HRP) in the presence of hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
162
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 27 publications
11
162
1
1
Order By: Relevance
“…Studies in vitro have shown the biodegradation of the oxidized-NTC by peroxidase enzymes such as horseradich peroxidase (HRP), human myeloperoxidase (MPO) and eosinophil peroxidase (EPO) under the presence of low concentration of H 2 O 2 and generating CO 2 as final product (Russier et al, 2011; . Zhao et al, 2011,Andon et al, 2013, Kotchey et al, 2013, Kagan et al, 2010.…”
Section: Biodegradation De Ntcmentioning
confidence: 99%
“…Studies in vitro have shown the biodegradation of the oxidized-NTC by peroxidase enzymes such as horseradich peroxidase (HRP), human myeloperoxidase (MPO) and eosinophil peroxidase (EPO) under the presence of low concentration of H 2 O 2 and generating CO 2 as final product (Russier et al, 2011; . Zhao et al, 2011,Andon et al, 2013, Kotchey et al, 2013, Kagan et al, 2010.…”
Section: Biodegradation De Ntcmentioning
confidence: 99%
“…On the other hand, today, there is no doubt that short, functionalized with polar moieties, and individualized MWCNTs offer a hope to be tested clinically [16]. But earlier in vitro [17] and in vivo [18] reports confirmed that, after functionalization, even >40 m long Fe@MWCNTs, providing individualized (i.e., not aggregated) nanotubes, could be considered as enzymatically degradable [19,20] and hence excretable drug vehicles [21].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study has shown that SWNTs are oxidized and degraded more efficiently when compared to MWNTs. 105 In addition, SWNTs with surface carboxyl groups are degraded efficiently when compared to pristine, ozone-treated and aryl-sulfonated SWNTs. 106 A greater degree of carboxyl functionalization, which considerably improves the hydrophilicity of the CNTs, leads to an improved rate of degradation.…”
mentioning
confidence: 99%